Kajian Aspek Kecepatan dan Ketepatan pada Sun Tracker Dua Sumbu Berbasis Sensor Berbentuk Tetrahedron - Saddam Azmi; Yuwaldi Away; Ira Devi Sara (Universitas Syiah Kuala, 2019)
The two-axis Sun tracker with the tetrahedron geometry that has been developed has an error percentage of 31.26% and a speed of 0.063 m/s. The value of the accuracy and speed is still considered low for tracking sunlight in open space conditions. The research aims to improve the accuracy and speed of the tetrahedron tracker sun. The method used to obtain tracking accuracy is to implement a control system that forms a tracking system using the proportional integral derivative (PID) control and modifies the sun's light by adding a sun tracker and laser to the top of the tetrahedron structure. In addition, the motor used to measure the state of the horizontal and vertical axes is the DC Stepper type. The results obtained indicate the level of accuracy of the modified sun tracker system is 0.650 on the X-axis and 0.540 on the Y-axis with a speed of 0.091 m / s. From these results, it can be concluded that the sun tracker modification is able to track sunlight properly with an average tracking error rate of 0.78% on the X-axis and 4.67% on the Y axis.